Facile preparation of TiO2/C nanocomposites as anode materials for lithium-ion batteries. Issue 2 (1st February 2016) - Jin, Shuangling; Zhang, Shimin; Zhang, Rui; Jin, Minglin
ABSTRACT: TiO2 /C nanospheres with diameter of 300–400 nm were synthesized by controlled thermal decomposition of titanium glycolate spheres in inert atmosphere. The effect of the calcination temperature and atmosphere on the structure and composition of the product are investigated. The products obtained by calcination of the precursor in nitrogen at 500°C consist of anatase and rutile nanoparticles, and amorphous carbon that is in situ generated from the organic components of glycolate precursor. When used as anode material for lithium-ion batteries, the as-prepared TiO2 /C nanocomposite delivers a capacity of 166 mAh/g after 250 charge/discharge cycles at a current rate of 0.2 C and give a good rate capability. The native carbon not only improves the local conductivity but also prevents the aggregation and growth of TiO2 nanoparticles during calcination, allowing efficient electronic conductivity and Li ion diffusion.